PENDEKATAN FAITH LEARNING DALAM PEMBELAJARAN MATEMATIKA - Hutagaol, Kartini (Jurnal Padegogik, 2018)
Teachers needs to be aware that there is no single way to learn the most correct,there is no way to teach the best or superior, because peoples are differ in intellectual abilities,attitudes, and personality. There can be no 'right test' way to study nor 'best' way to teach.Teachers are free to choose their own way and style in teaching and learning to achieve thegoals that have been determined by considering the conditions of each student. But there is alittle message in the particular subject matter of mathematics teaching in the classroom thatcreate an impression of each student when they leave the classroom students are expected todiscuss pleasant things which has happened, beside mathematics, to the new math coursefollowed, and it is expected that they will continue to smolder spirit until the next day. Thereforteachers need such effort and patience in providing the right motivation. Strong motivation inmathematics teaching is not just words, but stimulation through teaching techniques as theproper way to make students happy and more interested towards mathematics. The ways thatexpected to eliminate problems such as fear or mathematics anxiety, which is a commonproblem for many years. Faith based learning correlates learning particular subject matter inmathematics with the Word of God, students are directed always willing accept wisdom andknowledge of God. Teaching that leads to the heavenly teaching method to love God. Teachingin accordance with the criteria written in the book of Galatians 5:22-23, which are; love, joy,peace, patience, kindness, goodness, faithfulness, gentleness, and selfs control. ThePENDEKATAN FAITH LEARNING DALAM PEMBELAJARAN MATEMATIKAKartini HutagaolFakultas Keguruan dan Ilmu PendidikanUniversitas Advent Indonesiakartinih_smant@yahoo.com33expecttation by integrating faith in the teaching of mathematics is to form student Godlycharacter for present and eternal life to come.